(Not) wanting to choose: outside agencies at work in assisted reproductive technology. (November 2020) - Giraud, Anne-Sophie
Abstract: Human choice and interventions that could seem to threaten the course of 'nature' or 'chance' are at the heart of controversies over assisted reproductive technology across Western countries. These debates focus predominately on so-called 'selective reproductive technology'. While today, the technique of in-vitro fertilization (IVF) raises few political and bioethical debates in France and other Western countries, concerns remain that human intervention might replace 'natural' processes, threatening human procreation. These polemics focus on situations that require a decision, notably embryo selection and the fate of spare frozen embryos. The choices involved are induced by the technology and organized by the law. In the French legal system, IVF patients and professionals have the opportunity and, to a certain extent, the responsibility to decide on the status of in-vitro embryos. This article shows that, in these situations, both IVF patients and professionals invoke outside agencies ('instances tierces'), both to avoid making decisions and to recover a world order in which procreation is not entirely subject to human decision. In short, there is a need to feel that procreation is not entirely dependent on human intervention; that individuals do not decide everything. It appears that the choices that are made, their nature and the type of outside agency that is invoked are highly situated.